2012
DOI: 10.1016/j.jsat.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analyses of seven of the National Institute on Drug Abuse's principles of drug addiction treatment

Abstract: Seven of the 13 Principles of Drug Addiction Treatment disseminated by the National Institute on Drug Abuse (NIDA) were meta-analyzed as part of the Evidence-based Principles of Treatment (EPT) project. By averaging outcomes over the diverse programs included in EPT, we found that five of the NIDA principles examined are supported: matching treatment to the client’s needs; attending to the multiple needs of clients; behavioral counseling interventions; treatment plan reassessment; and counseling to reduce risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 35 publications
0
17
1
Order By: Relevance
“…First, intranasal users remained in treatment longer than smokers of cocaine, which was consistent even after removing the sample of methadone-maintained participants, who are likely to remain in treatment longer due to the need for daily opioid maintenance medications. While the effectiveness of treatment retention toward improvement in drug use remains questionable (Pearson et al, 2012), treatment retention is often cited as a key outcome measure and several lines of research have reported positive relationships between treatment duration and drug use outcomes (C.-Y. Chen & Lin, 2009; De Giorgi et al, 2012; Khalsa, Tashkin, & Perrochet, 1992; Ruiz, Cleary, Nassiri, & Steele, 1994; Welch, Todd, & Krause, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…First, intranasal users remained in treatment longer than smokers of cocaine, which was consistent even after removing the sample of methadone-maintained participants, who are likely to remain in treatment longer due to the need for daily opioid maintenance medications. While the effectiveness of treatment retention toward improvement in drug use remains questionable (Pearson et al, 2012), treatment retention is often cited as a key outcome measure and several lines of research have reported positive relationships between treatment duration and drug use outcomes (C.-Y. Chen & Lin, 2009; De Giorgi et al, 2012; Khalsa, Tashkin, & Perrochet, 1992; Ruiz, Cleary, Nassiri, & Steele, 1994; Welch, Todd, & Krause, 1991).…”
Section: Discussionmentioning
confidence: 99%
“… viii We did not identify and analyze services intended to address “drug use needs” (“ (but see Pearson et al 2012) To do so would have required a detailed review of literature to identify “needs” associated with post-treatment drug use, which was beyond the scope of the study. …”
Section: Notesmentioning
confidence: 99%
“…Although empirical replications of Risk × Treatment Interactions are needed to confirm principled findings, evaluation research is being extended to concentrate on the characteristics of offenders in which programming can be designed to have its optimal effect with regard to recidivism reduction. Generally, 240 D. Routh and Z. Hamilton interventions that incorporate RNR into participant selection and program design are identified to improve reentry outcomes upon release (Pearson et al, 2012;Prendergast, Pearson, Podus, Hamilton, & Greenwell, 2013).…”
Section: Improving Programming Provision Via Rnrmentioning
confidence: 99%